Young Minority Home‐Language Students' Biased Reading Self‐Concept and Its Consequences for Reading Development. Issue 1 (28th February 2020) - Segerer, Robin; Niklas, Frank; Suggate, Sebastian; Schneider, Wolfgang
Abstract: Young students who speak a different language at home than that spoken in school (i.e., a minority home‐language) appear to exhibit a biased reading self‐concept. Importantly, this biased reading self‐concept may correspond with altered causal pathways between reading self‐concept and achievement in minority home‐language students. To test this idea, the authors examined cross‐lagged links between reading self‐concept and reading achievement in a large multiple‐group longitudinal study in Germany. Students with German ( n  = 885), Turkish ( n  = 193), or another ( n  = 550) home language were tested yearly in grades 1–4 on measures of reading and reading self‐concept. Despite showing lower reading achievement, students speaking a minority home language exhibited a higher reading self‐concept. Cross‐lagged paths revealed reciprocal effects between reading achievement and reading self‐concept from grade 1 to grade 2, particularly for students with German as a home language. Minority home‐language students showed significantly lower effects of reading achievement on their subsequent reading self‐concept from grade 1 to grade 2. From grade 2 onward, reading achievement predicted reading self‐concept, but not vice versa.